The role of fiscal incentives in promoting energy efficiency in the industrial sector: Case studies from Asia - Tapan Sarker; Farhad Taghizadeh-Hesary; Aline Mortha; Anjan Saha (Asian Development Bank Institute (ADBI), 2020)
In recent years, awareness about climate change and the need for cutting greenhouse gas (GHG) emissions has spread. Policymakers have hence chosen to promote the use of renewable energy, as well as encouraging improvements in energy efficiency (EE). This study analyzes the policy strategies of four Asian countries with large GHG emissions and EE strategies, namely the People's Republic of China (PRC), India, Indonesia, and Japan. The study first reviewed the types of instruments that can be used to reduce energy intensity, namely incentivizing policies (subsidies, tax reductions, voluntary agreements, ETSs and cooperative schemes), market-based instruments (MBIs) (white certificates and tendering schemes), and EE finance (special credit lines and risk-sharing facilities). Through a careful review of the literature, the study identified advantages and weaknesses, as well as the effectiveness of said policies in the case studies. The study highlighted the role of voluntary agreements and careful planning in successfully improving EE in the PRC. MBIs have also been shown to efficiently reduce energy intensity. On the other hand, direct subsidies represented a heavy burden on the government's budget, with limited results. Despite their lack of direct results, cooperative schemes and the role of finance in improving EE should not be overlooked.
Keywords: Q48; Q54; Q56; 330; energy efficiency; energy policy; Asia; climate change